Effect of nutritional status on Rohingya under-five children in Bangladesh - Md Hasib; Md. Nazmul Hassan; Mehedi Hasan; Md. Shafiqul Islam Khan (Intelektual Pustaka Media Utama, 2020)
The extent of nutritional status affecting Rohingya refugee under-five children has become a major health issues in Bangladesh. This study aimed to investigate the nutritional status and its effect on under-five Rohingya children in comparison with the areas of Bangladesh. A cross-sectional study of 300 under-five children were conducted by structured questionnaire from Rohingya camp (100), Cox’s Bazar (100) and Dumki (100) applying simple random method. Anthropometric indices (weight, height, mid-upper arm circumference (MUAC)) were measured in children aged 6-59 months. Indices were reported in z-scores and compared with WHO 2005 reference population. Data were analyzed by WHO Anthro-Plus Software and SPSS. About 41% Rohingya, 43% surrounding areas, and 46% Dumki were stunting in height-for-age z-score (HAZ) score respectively. Near about 13%, 11% and 4% were wasting in weight-for-height z-score (WHZ) score and 18%, 15% and 10% were underweight in weight for age Z-score (WAZ) score respectively. Food groups, Disease, worm infestation among 3 study areas were statistically significant (P< .05). Moreover, handwashing practice, vitamin-A consumption and worm infestation effects among diseases were statistically significant. In this study population, there was high prevalence of malnutrition among Rohingya children, especially wasting and underweight compared to other areas. Prevention of malnutrition plays an important role for having a healthy society of Rohingya Refugees.